Association of visit-to-visit HbA1c variability with cardiovascular diseases in type 2 diabetes within or outside the target range of HbA1c - Sun, Bao; Gao, Yongchao; He, Fazhong; Liu, Zhaoqian; Zhou, Jiecan; Wang, Xingyu; Zhang, Wei (Frontiers in Public Health, 2022)
Background Although a growing attention has been recently paid to the role of HbA1c variability in the risk of diabetic complications, the impact of HbA1c variability on cardiovascular diseases (CVD) in type 2 diabetes is still debated. The aim of the study is to investigate the association of HbA1c variability with CVD in individuals within or outside the target range of HbA1c. Methods Using data from Action in Diabetes and Vascular disease: preterAx and diamicroN-MR Controlled Evaluation (ADVANCE), we enrolled 855 patients with type 2 diabetes in China. The primary outcomes included major macrovascular events and major microvascular events. Visit-to-visit HbA1c variability was expressed as the coefficient of variation (CV) of five measurements of HbA1c taken 3–24 months after treatment. Cox proportional hazard models were used to estimate adjusted hazard ratios (aHR). Results Among 855 patients in the intensive glucose treatment group, 563 and 292 patients were assigned to the group of “within the target range of HbA1c” (WTH) (updated mean HbA1c ≤ 7.0%) and “outside the target range of HbA1c” (OTH) (updated mean HbA1c > 7.0%), respectively. HbA1c variability was positively associated with the risk of major microvascular events in all patients and both the subgroups during a median follow-up period of 4.8 years. Particularly, the risk related to HbA1c variability was higher in patients in WTH group for the new or worsening nephropathy [aHR: 3.35; 95% confidence interval (CI): 1.05–10.74; P = 0.042]. Conclusions This retrospective cohort study confirmed the positive correlation between HbA1c variability and major microvascular events, especially in subjects in WTH or OTH.